Match Injury Incidence for a New Zealand Amateur Domestic Female Soccer Team over Two Consecutive Seasons - Doug A. King; Patria A. Hume; Trevor N. Clark (MDPI AG, 2024)
Objective: To determine the match injury incidence for a New Zealand amateur domestic female soccer team over two consecutive seasons. Methods: A descriptive, epidemiological observational study was conducted to determine match injury incidence for 49 players over two domestic seasons. Match exposure and injury burden were calculated. Results: A total of 84 match-related injuries resulted in a match injury incidence of 145.5 (95% confidence interval (CI): 117.4 to 180.1) per 1000 match h. Attackers had a higher incidence of injuries for total (200.0 per 1000 match h) and missed matches (152.4 per 1000 match h). The lower limbs had the highest injury incidence (105.6 per 1000 match h), with ankle injury being the most reported (43.3 per 1000 match h) lower limb injury. Over three quarters (75.3%) of the injuries recorded were missed match injuries. Sprains/strains were the most recorded total (86.6 per 1000 match h) injury type. Fractures were recorded as having the highest mean injury burden (68.7 ± 70.4 days). Discussion: Historically, there was a paucity of injury burden data for female football; however, the data presented within this study can be utilised to support the identification of injury patterns and areas to be included within injury reduction programmes.